In field evaluation of injectable appramycin for the control of naturally occuring colibacillosis in young calves - ΚΥΡΙΑΚΗΣ Σ.; ΣΑΡΡΗΣ Κ.; ΑΝΔΡΕΩΤΗΣ Ι.; ΤΣΑΛΤΑΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The efficacy of apramycin at 20mg/kg of body weight IM for 5 days was evaluated for the control of naturally oecuring colibacillosis in young calves (n,=20). Positive control calves (n ,=20) were treated with trimethoprim sulphadiazine and when symptoms persisted or recurred with Oxytetracycline and/or chloramphenicol IM at dosages and for periods recommented by the manufacturers. Scored clinical observations and diarrhoea were generally comparable between the two treatment groups. Due to persistence or recurence of diarrhoea, positive control calves required a total of 160 IM injections as compared to 100 IM injections for apramycin group. The average daily gain of the apramycin calves was greater, although not significant (P 0.05), for the periods 0-7 days and 7-14 days by 123.33% and 23.51% respectively. The overall improvement (0-14 days) was statistically significant (Ρ 0.05) amounting to 44.6% over the controls. Mean serum immunoglobulin levels did not differ significantly (P 0.05) between the two treatment groups. From fecal swabs taken from all calves on trial days 0 and 5, E. colt was isolated and 9 strains were recognised enteropathogenic belonging to 4 serotypes.